Haematology an illustrated colour text - Howard, Martin; Hamilton, Peter J. (Illustrated colour text, 2013)
This textbook on haematology in the Illustrated Colour Text series is suitable for medical students, junior doctors and others needing a concise and practical introduction to the subject. Concise and manageable coverage of the major blood diseases and their treatment. Does not overload the reader with science, unlike some competing books. Focus is on the haematology patient and on the practical aspects of the subject. Makes use of the attractive features of the ICT series - double page spreads, lots of colour illustrations, summary boxes